Isothermal Investigation of Copper(II) and Nickel(II) Adsorption from Water by Novel Synthesized Polyaniline Composites with Polyalthia longifolia and Alastonia scholaris Dried Leaves - Kanwal, Farah; Rehman, Rabia; Samson, Sumbal; Anwar, Jamil (Asian Journal of Chemistry, 2013)
The preparation of polyaniline composites with Polyalthia longifolia and Alastonia scholaris was done in this research work. These composites were characterized by UV/visible and FT-IR spectroscopy and after that they were employed for adsorptive removal of Cu(II) and Ni(II) from aqueous medium on batch scale. The suitability of the data was tested with Langmuir and Freundlich models of isotherm. Maximum sorption capacities of polyaniline/Alastonia scholaris composites for removing Ni(II) and Cu(II) are: 16.17 and 31.25 mg/g respectively, while in case of polyaniline/Polyalthia longifolia composites for removing Ni(II) and Cu(II) are: 11.64 and 28.21 mg/g respectively. Thermodynamic studies showed that sorptive removal of Cu(II) and Ni(II) by these composites occur spontaneously because Polyalthia longifolia and Alastonia scholaris modified the morphology of polyaniline by preventing its aggregation and improving its adsorption capacity.